Automatización de un módulo de transporte de fluido hidráulico para el laboratorio de Ingeniería Hidráulica de la Universidad Técnica de Cotopaxi en el periodo 2021. - Kevin Johannes, Armas Gavilanes (2021)
The faculty of engineering and applied sciences sees the need to automate a hydraulic fluid transport module in order to monitor, measure and visualize the behavior of electrical and hydraulic parameters in laboratory tests. The module is composed of three PVC pipe sections, with different diameters and fittings. First, theoretical information is collected on the parameters that influence the study, friction losses in pipes and fittings. For the automation of the module a Programmable Logic Controller was used, which with the help of communication protocols it is possible to link and obtain the electrical parameters measured by the energy analyzer. The hydraulic parameters are measured by flow and pressure sensors which will be displayed on a digital screen in real time. Thanks to a Web server it is possible to export a database and compare the variation of the study parameters when opening different valves of the module. Finally, when performing laboratory tests, it is obtained higher pump consumption when the module valves are open at 45˚, different values in the electrical and hydraulic parameters depending on the sections that are in operation, the experimental friction losses in pipes and fittings are compared with theoretical results obtaining the percentage of error.